Sistemas de liberação controlada de nutracêuticos- liberação in vitro de magiferina a partir de microesferas de pectina/quitosana - Souza, José Roberto Rodrigues de (2008)
Incorporation of nutraceuticals compounds such as vitamins, probiotics, bioactive peptides and antioxidants in food systems provides a simple way to develop new functional foods that can have physiological benefits or reduce risks of disease. Pectins have been investigated for their ability to produce spheres of calcium pectinate gels containing bioactive. Chitosan has also been widely used in the preparation of beads due to its mucoadhesive properties. In this study, three types of spheres of pectin/calcium/chitosan with different degrees of reacetylation were produced in order to encapsulate a powerful natural antioxidant extracted from mango, mangiferin. Initially, two samples of citrus pectin were characterized by FTIR, 1H NMR, Rheology and GPC. The citrus pectin with the lowest degree of methoxylation was chosen for the preparation of beads due to its better gelling properties. The beads produced were characterized by FTIR, SEM and swelling. The formation of the reacetylated complex pectin/calcium/chitosan was observed by FTIR and SEM. A study of controlled release of mangiferin was conducted from three types of beads obtained by two different methodologies. The values of percentage of release were quite significant, reaching up to 75%. The mechanisms behaviour for the release of mangiferin from spheres of pectin/calcium/chitosan showed that the bioactive was released from the matrix mainly through relaxation of the polymer chains.